Recent Progress in Fiber Reinforced Polymer Hybrid Composites and Its Challenges-A Comprehensive Review - C. M. Mohanraj; R. Rameshkumar; Mathanbabu Mariappan; Ashokkumar Mohankumar; Barathiraja Rajendran; P. Senthamaraikannan; Indran Suyambulingam; R. Kumar (Journal of Natural Fibers)
Global warming and natural calamities have driven scientists and researchers to explore renewable and eco-friendly raw materials for industrial and other applications. Traditionally, structural components in various fields are made of plastic, which is harmful to the environment, or heavy metallic materials, which consume excessive energy during dynamic operations, leading to increased fossil fuel consumption. Composite materials have emerged as a promising substitute for these environmentally detrimental materials. Among them, plant-based fiber-reinforced polymer composites, derived from renewable and abundant natural fibers, have gained significant attention due to their environmental benefits, cost-effectiveness, and potential for sustainability. Recent trends in this field include the development of hybrid composites, the incorporation of advanced biopolymers, and improved processing techniques to enhance mechanical and thermal performance. However, challenges such as interfacial bonding, water absorption, and durability under extreme conditions still hinder their broader adoption. This review explores the advancements in plant-based fiber-reinforced polymer composites, emphasizing recent progress, ongoing challenges, and future potential. It aims to provide comprehensive insights for researchers and practitioners focusing on this rapidly evolving domain.